(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Social workers have historically found employment in the hospital industry, and they are valuable members of the healthcare team. Due to the growing recognition of the critical relationship between the biophysical aspects of health and the surrounding psychosocial circumstances which call for multidisciplinary interventions and the involvement of specialized social work personnel to deal with such issues social work practitioners have become more and more involved in hospital work. By examining whether the traits and responsibilities of modern professional social workers who work in the healthcare industry in western Saudi Arabia are meeting best practices, the study aims to add to the body of knowledge.